DO LARGE PRETERM INFANTS WITH RESPIRATORY DISTRESS SYNDROME BENEFIT FROM EARLY SURFACTANT? - N Khosravi; p Mohagheghi (Acta Medica Iranica, 2008)
Large preterm infants are generally not considered good candidates for surfactant treatment until they have been intubated for progressing respiratory distress. This study has been done to detect the effect of electively providing early single-dose surfactant to large preterm babies with mild to moderate respiratory distress syndrome (RDS). A randomized clinical trial was performed on 45 infants with birth weight > 1250 grams, gestational age < 36 weeks, postnatal age 0-12 hours, FiO2 > 40% and no immediate need for intubation. They were randomly divided into two interventional (n = 22) and control (n = 23) groups. Interventional group infants were intubated and received surfactant in the first 12 hours of life with signs of mild to moderate RDS and were extubated as soon as possible. The control group infants were only intubated and received surfactant when clinically or radiographically indicated. The primary outcome was duration of assisted ventilation. Interventional group infants had a median duration of assisted ventilation of 4.45 hours compared to 1.02 hours in the control group in the first 24 hours of life, since only 8 of 23 infants in the control group (34%) needed intubation and mechanical ventilation. There were no differences in the two groups for need of subsequent retreatment with surfactant and requirement for supplemental oxygen or mechanical ventilation, hospital stay and adverse outcomes. Results of this study indicate that elective intubation for administration of early single-dose surfactant to large preterm infants is not necessary.